Structural and metrological aspects of piston-type gas-measuring units (gas piston prover) - Бас, Олександр Анатолійович (Technology audit and production reserves, 2014)
The article describes development and combination of a drive unit of primary standard of gas volume and volume flow units at the pressure of 1,6 MPa, which is a synthesis of power-speed reduction gear transmissions. The optimal design of a drive unit is application of a complex of gear reducers, where a reducer with cylindrical gear, with variable stepped transmission ratio, with reverse gear is used for high-speed transmission, while for power transmission a reducer with bevel gear, with hypoid gear, with involute profile of helical teeth is used. Oriented values of transmission ratios of gear drives are calculated on basis of the input data, i.e. a number of values of gas volume flow, selected for calibration (certification) of gas meters within the range from 4 m3/hour to 200 m3/hour. The general kinematic scheme of primary standard is worked out, the metrological aspect is considered and complex indices of kinematic accuracy of applied reducers of the drive unit are calculated in the article.